An exploration of eating behaviours and caregiver mealtime actions of children with Tourette syndrome - Smith, Bobbie L.; Ludlow, Amanda K. (Frontiers in Pediatrics, 2022)
Food avoidant behaviours are common concerns amongst individuals with Tourette syndrome, with high levels of food selectivity reported in children and food neophobia and avoidant restrictive eating behaviours in adults. However, less is known about food approach behaviours. The current study aimed to explore differences in food approach and food avoidant eating behaviours in children with Tourette syndrome (TS) and their relationship to caregiver mealtime actions. Thirty-seven caregivers of children with Tourette syndrome were compared with children with Autism Spectrum Disorders, children with Attention-Deficit/Hyperactivity Disorder and a control group. Caregivers completed the Child Eating Behaviour Questionnaire and Parent Mealtime Action Scale-Revised. Caregiver-reported findings revealed that children with Tourette syndrome exhibited more food approach behaviours, specifically greater food responsiveness, emotional overeating and desire to drink, compared to controls. Children from the three neurodiverse groups had similar levels of emotional overeating and food selectivity, which were all significantly higher than the control group. Positive persuasion was uniquely identified as a mealtime strategy adopted by caregivers of children with Tourette syndrome. The results suggest that children with Tourette syndrome are at more risk of showing a broader array of food difficulties than previously reported, including food avoidant and approach behaviours. It is encouraged that clinicians monitor eating behaviour in appointments with children with Tourette syndrome.